Identification and Characterization of the Corazonin Receptor and Possible Physiological Roles of the Corazonin-Signaling Pathway in Rhodnius prolixus - Hamoudi, Zina; Lange, Angela B.; Orchard, Ian (Frontiers in Neuroscience, 2016)
Neuropeptides control many physiological and endocrinological processes in animals, acting as neuroactive chemicals within the central and peripheral nervous systems. Corazonin (CRZ) is one such neuropeptide that has a variety of physiological roles associated with control of heartbeat, ecdysis behavior initiation, and cuticle coloration. These physiological effects are mediated by the CRZ receptor (CRZR). In order to understand the role of the CRZ-signaling pathway in Rhodnius prolixus, the cDNA sequence encoding the Rhopr-CRZR was isolated and cloned revealing two splice variants (Rhopr-CRZR-α and β). Sequence analysis revealed characteristics of rhodopsin-like GPCRs. Rhopr-CRZR-α and β were dose-dependently activated by Rhopr-CRZ with EC50 values of 2.7nM and 1nM, respectively, when tested in a functional receptor assay using CHOKI-aeq cells. Neither receptors were activated by the evolutionarily-related peptides, Rhopr-AKH or Rhopr-ACP. For fifth instars, qPCR revealed expression of Rhopr-CRZR transcript in the CNS, the dorsal vessel, abdominal dorsal epidermis, and prothoracic glands with associated fat body. Interestingly, transcript expression was also found in the female and male reproductive tissues. Rhopr-CRZR transcript was reduced after injection of dsCRZR into adult R. prolixus. In these insects, the basal heartbeat rate was reduced in vivo, and the increase in heartbeat frequency normally produced by CRZ on dorsal vessel in vitro was much reduced. No effect of dsCRZR injection was seen on ecdysis or coloration of the cuticle.